Highly hydrophobic silanized melamine foam for facile and uniform assembly of graphene nanoplatelet towards efficient light-to-thermal energy storage. (August 2022) - Akhiani, Amir Reza; Cornelis Metselaar, Hendrik Simon; Ang, Bee Chin; Mehrali, Mehdi; Mehrali, Mohammad
Abstract: Solar-thermal technology based on phase change materials (PCMs) has received a lot of attention as a cost-effective and practical way to overcome solar energy intermittency. However, weak photothermal conversion ability and complex preparation processes have hindered the practical application of PCMs. In this work, a new approach for facile, uniform, and firm assembly of graphene nanoplatelet (GNP) through the reaction of graphene oxide (GO) with the silanized melamine foam (MF) is introduced. Here, the deposited amino siloxane layer not only promotes the adhesion and integrity of embedded GNP/GO nanosheets but also facilitates the synthetic route compared to the previous studies. Following the reduction of GO with oleylamine (OA), the hybrid GNP/rGO foams with an integrated network were obtained. The composite PCMs were prepared through the incorporation of paraffin wax (PW) into the hybrid structure. The high hydrophobicity and porosity of the GNP/rGO foams resulted in a high loading of paraffin wax (nearly 97 wt%) and thus large transition enthalpy of 182 J g -1 . The GNP/rGO framework provided excellent solar-thermal storage efficiency of up to 92.2%. The PCM composite containing the highest content of GNP (6 wt%) revealed an enhanced thermal conductivity by 87% compared to the unmodified MF/PW composite. Graphical abstract: Image 1 Highlights: GNP/rGO foam is facilely prepared by introducing active amino groups onto the MF structure. The highly hydrophobic foam prevents the leakage of PW during phase transition. An Integrated GNP/rGO network acts as a photon captor and heat conductor. The solar-thermal conversion efficiency can reach 92.2% by incorporating GNP/rGO network.